Phosphorus partitioning contribute to phosphorus use efficiency during grain filling in Zea mays - Sun, Yan; Han, Yang; Xu, Zikai; Zhang, Jinting; Shen, Jianbo; Cheng, Lingyun (Frontiers in Plant Science, 2023)
Lower phosphorus (P) availability limits crop productivity in agroecosystems. The remobilization of P from source to sink organs plays an important role in enhancing P-utilization efficiency of crops. During the grain filling stage, phosphorus flow to the developing grainsthe primary sink -determines crop yield. However, the specific contribution of different organs to grain P throughout the post-silking period in maize remains unclear. In our study, three maize inbred lines (CIMBL89, Ji846 and CML118) with contrasting P status were selected and grown in the field with high P (HP, 150 kg ha -1 P2O5) and low P (LP, 0 kg ha -1 P2O5) conditions. The grain yield of CIMBL89 was 69% and 169% greater at HP supply, and83% and 309% greater than that of Ji846 and CML118 at LP supply, respectively. The ear length, ear diameter and kernel row number of CML118 were lower than those of CIMBL89 and Ji846 at HP supply. Most of P (87%) in the grain of CIMBL89 came from P uptake at LP supply, while almost all P (95%) came from P remobilization in various organs at HP supply after silking. In contrast, 91% of the P found in the grain of CML118 came from P remobilization at LP supply, while 76% came from P uptake at HP supply after silking. In conclusion, our findings suggest that CIMBL89, with greater P acquisition efficiency, contributes to grain formation and production during the post-silking period under LP supply. Additionally, CIMBL89 has the ability to fully remobilize P and avoid extravagant absorption of P in P-sufficient soil, which sets it apart from Ji846 and CML118.